METTL3/m6A/IFIT2 regulates proliferation, invasion and immunity in esophageal squamous cell carcinoma - Fangfang Ge; Fangfang Ge; Zhenyu Li; Zhenyu Li; Jiaru Hu; Youguang Pu; Fangfang Zhao; Lingsuo Kong (Frontiers Media S.A., 2022)
Epigenetic regulation plays a critical role in the development, progression, and treatment of tumors. The most common chemical modification of mRNA, called m6A, is essential for controlling mRNA stability, splicing, and translation. Methyltransferase-like 3 (METTL3) is an important m6A methyltransferase. The mechanism of action of METTL3 in esophageal squamous cell carcinoma (ESCC) remains unclear. In this investigation, we sought to clarify the function and clinical importance of METTL3 in ESCC and investigate its underlying mechanisms. We discovered that METTL3 has a significant proliferative effect in ESCC cells by using lentiviral construction of stable cell lines overexpressing METTL3 (METTL3-OE) and knocking down METTL3 (sh-METTL3). To create a xenograft tumor model, we inoculated KYSE510 cells subcutaneously into BALB/c nude mice and discovered that sh-METTL3 inhibited the tumorigenicity of esophageal cancer KYSE510 cells in the nude mouse tumor model. MeRIP-seq and RNA-seq analysis revealed IFIT2 to be a METTL3 target gene. The findings revealed that METTL3 regulates IFIT2 and thus influences malignant biological behaviors such as proliferation, migration, and invasion of ESCC, as well as the immune microenvironment of tumors.